Konstruksi Pemikiran Muhammad Yunan Yusuf Dalam Tafsir Annahu ‘L Haq - Hendriyan Rayhan (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The writing of tafsir (Quranic interpretation) in Indonesian has emerged since the early 20th century. To this day, scholars and scholars continue to produce works on Quranic studies. One figure in this century who has been prolific in writing tafsir in Indonesian is Muhammad Yunan Yusuf. He first wrote a tafsir for juz 30, then went back to the previous juz. One of Yunan Yusuf's works is the tafsir Annahu 'l Haq, which contains an interpretation of juz 25. Using content analysis methods, this paper examines the construction of Yunan Yusuf's thinking in his tafsir. The name Annahu 'l Haq is taken from the central theme of this juz, which emphasizes that the Quran is true. The construction of thought is found in the linguistic style, the scientific style, and the Islamic thought style used. Keywords: Indonesian Tafsir, Yunan Yusuf, construction